PEMBUATAN APLIKASI PENDATAAN VAKSINASI BERBASIS DESKTOP MENGGUNAKAN VISUAL BASIC 2010 DAN MySQL - Gina Dewi Sonia; Adzim Fathalul Anhar (Jurnal Fakultas Teknik Kuningan, 2022)
There are obstacles to the distribution of vaccinations in public officials, public officials include the lack of public understanding and knowledge, access to health services, and the lack of vaccine availability. In addition to the lack of public understanding about the importance of vaccination and the amount of untrue news out there about vaccinations, people are becoming wary. Therefore, the presence of the development of information system technology based on Desktop and Visual Basic is expected to help provide solutions to the problems that exist in Panawuan Village.The design in building this system is divided into Data Flow Diagrams, use case diagrams, and interface design. This application is desktop based and designed using Visual Basic programming language, MySQL. This application development uses visual basic, which uses black box testing. The result of this research is a desktop application and visual basic. The conclusion of this study is to facilitate the Panawuan Village Government, CIgandamekar District, Kuningan Regency in presenting report data effectively and efficiently. As well as making it easier for the public to get vaccination information in Panawuan Village.